Implementation of creative self-efficacy as moderation: extrinsic and intrinsic motivation to creative behaviour in the women entrepreneur context - Safrizal, Helmi Buyung Aulia; Mustika, Hindah; Ximenes, Mateus (BISMA (Bisnis dan Manajemen), 2024)
The aim of this research is to examine and analyse the moderation role of creative self-efficacy on the influence of extrinsic and intrinsic motivation on creative behaviour in the context of creative industries i.e., Madurese batik. Madurese batik is a heritage and has its own uniqueness because Madurese batik is a form of history that must be maintained for its sustainability. This research used a quantitative approach to test and analyse the influence of motivation on creative behaviour, with creative self-efficacy as a moderator. This study tests the conceptual model that has been formed based on the behavioural theory, which is the grand theory for the formation of the research model. The data collected from 310 women who make typical batik were then tested using (SEM-PLS). The results show that all hypotheses are proven. Extrinsic and intrinsic motivation indirectly influence creative behaviour; creative self-efficacy is able to be a moderator in the influence of motivation (extrinsic and intrinsic) on creative behaviour. The results indicate that the success of creative behaviour is due to strong motivation, so this becomes an important part of women's creative activities. The novelty of this study is the ability of creative self-efficacy to moderate the relationship of motivation toward creative behaviour. Self-efficacy has an important role in carrying out certain behaviours.